Stimulating awareness of Precision Farming through gamification: The Farming Simulator case - Pavlenko, Tetiana; Argyropoulos, Dimitrios; Arnoult, Matthieu; Engel, Thomas; Gadanakis, Yiorgos; Griepentrog, Hans W.; Kambuta, Jacob; Latherow, Tamisan; Murdoch, Alistair J.; Tranter, Richard; Paraforos, Dimitrios S. (My University, 2024)
Precision Farming (PF) provides different solutions to assist the decision-making process on farms. Current PF technologies such as variable rate site-specific applications can bring financial benefits to farmers as well as environmental advantages. Increasing scientific research and an expanding number of PF products are supporting a growing interest in PF applications. However, the actual implementation of these technologies on farms in many cases remains low. Therefore, there is a need to disseminate and transfer knowledge about the positive aspects of PF. One of the ways to facilitate the adoption process of PF technologies is education and training among farmers and other interested stakeholders. This paper presents a case study using the computer game Farming Simulator as an educational tool for raising awareness about the topic in an engaging and enjoyable way. Two distinct downloadable content (DLC) versions were developed and implemented in the versions 2019 and 2022 of the game, respectively, each with a range of PF functionalities (automatic steering, variable rate applications, yield mapping among others). The PF DLCs have received positive feedback from students and scientists but also the general public. The growing number of downloads (3,661,069 in total for both DLC versions as of 15th November 2023) demonstrates the effectiveness of computer games as an educational tool to educate and inform stakeholders (farmers, scientists, students, and the general public) about agricultural challenges and the potential of PF as a solution.
Keywords: Adoption; Gamification; Variable rate; Site-specific